PROBLEMATIKA LITERASI DIGITAL GURU MATEMATIKA : STUDI KASUS IMPLEMENTASI KURIKULUM MERDEKA DI SMP KABUPATEN CILACAP - Dwi Andriyani; Mahdia Silmi Aziz; Kusno Kusno (MUST: Journal of Mathematics Education, Science and Technology, 2026)
This study aims to analyze the problems of digital literacy among mathematics teachers in implementing the Merdeka Curriculum in secondary schools. The research employed a qualitative approach with a case study design involving five mathematics teachers in Cilacap Regency selected through purposive sampling. Data were collected using semi-structured questionnaires consisting of Likert-scale items and open-ended questions, and analyzed through descriptive qualitative and thematic analysis techniques. The findings indicate that teachers' digital literacy is generally at a good level, with the highest scores recorded for digital device usage (M = 4.8; very good category) and digital ethics (M = 5.0), yet a significant gap was identified in technical troubleshooting competence (M = 3.4; fair category). More critically, teachers' proficiency in mathematics-specific software including GeoGebra for geometry concept visualization and function exploration, and Desmos for interactive mathematical representation reached only an average score of 4.0, the lowest dimension among all measured application competencies. This finding indicates that technology integration in mathematics learning has not been optimally leveraged, particularly in supporting students' understanding of abstract mathematical concepts through interactive tools. Furthermore, teachers continue to face several challenges, including limited infrastructure and digital devices, difficulties in integrating technology with mathematical concepts, and time constraints due to high workloads. The implementation of differentiated learning within the Merdeka Curriculum also remains a significant challenge. Despite these limitations, teachers demonstrate adaptive capacity by applying digital learning strategies such as blended learning, gamification, and project-based learning. This study concludes that the problems of teachers' digital literacy are multidimensional and require a comprehensive approach through strengthening digital pedagogical competence, institutional support, and adequate infrastructure provision.